2022
DOI: 10.1021/acsaelm.2c01222
|View full text |Cite
|
Sign up to set email alerts
|

Developing Subthreshold-Swing Limit of PEALD In–Sn–Ga–O Transistor via Atomic-Scaled Sn Control

Abstract: The In−Sn−Ga−O (ITGO) thin-film transistor (TFT) is promising in that it possesses enhanced electrical characteristics and stability because the tin (Sn) has large spherical s orbitals and a high binding energy with oxygen (O). Recently, there have been several reports of ITGO material fabricated via sputtering. Therefore, studies that control Sn composition to achieve unique characteristics and obtain conformal films have been limited. For these reasons, we evaluated plasma-enhanced atomic layer deposition (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Particularly, the device with the GI grown at 400 °C showed an SS of 61 ± 1 mV/decade, which is comparable to the theoretical minimum value of 60 mV/decade. An extremely low SS indicates that defects in the active layer and interface between the active layer and GI were minimized by the GI deposition temperature after high-temperature annealing. , In addition, μ FE gradually increased from 17.2 to 27.6 cm 2 /Vs with increasing GI deposition temperatures. Several researchers have reported that the increase in μ FE and on-current ( I on ) is closely related to the tail state of the conduction band .…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the device with the GI grown at 400 °C showed an SS of 61 ± 1 mV/decade, which is comparable to the theoretical minimum value of 60 mV/decade. An extremely low SS indicates that defects in the active layer and interface between the active layer and GI were minimized by the GI deposition temperature after high-temperature annealing. , In addition, μ FE gradually increased from 17.2 to 27.6 cm 2 /Vs with increasing GI deposition temperatures. Several researchers have reported that the increase in μ FE and on-current ( I on ) is closely related to the tail state of the conduction band .…”
Section: Resultsmentioning
confidence: 99%
“…With the growing interest in ALD, studies on materials using ALD have also rapidly increased, as shown in the table, which will be discussed in this review. In particular, superior electrical performances have been recently reported, including a remarkable mobility of over 100 cm 2 V −1 s −1 [43,46], an exceptionally low subthreshold swing under 100 mV/decade [64,66,80,83], and highly improved stability using a stack structure [14]. However, the main benefits of employing ALD for oxide semiconductor channel TFTs have not been clearly suggested.…”
Section: Value Of Ald As a Fabrication Process For Oxide Semiconducto...mentioning
confidence: 99%
“…Using table 1, we determined that studies of indium-based oxide semiconductors have greatly increased since 2021. Not only binary In 2 O 3 [42][43][44][45][46][47][48][49], but also a ternary as IGO [59][60][61][62], IZO [62,63], In-Al-O (IAO) [64,65] and ITO [66], quaternary as IGZO [4,30,[71][72][73][74][75][76][77][78][79][80], ITAO [81,82], and ITGO [83] have been introduced. Also, compared to other materials in table, the precursors for indium oxide are variously used.…”
Section: Chemical Reaction and Film Propertiesmentioning
confidence: 99%
“…Conversely, only one atomic layer is deposited by one cycle of plasma-enhanced atomic layer deposition (PEALD), [28] and it is very easy to finetune the composition ratio of the oxide thin film. [14,29,30] In particular, the super-cycle PEALD method, in which each atomic layer is deposited alternately, can control the ratio of elements in the thin film by adjusting the ratio of the number of cycles of the atomic layer. Therefore, PEALD can provide an excellent method to inject Al into IAZO and control its amount.…”
Section: Introductionmentioning
confidence: 99%